Intramyocardial Dissection following Postinfarction Ventricular Wall Rupture Contained by Surrounding Postoperative Adhesions - Abdulkadir Ercan; Orcun Gurbuz; Gencehan Kumtepe; Hakan Ozkan; Ilker Hasan Karal; Yusuf Velioglu; Serdar Ener (Case Reports in Surgery)
Introduction. Dissection of the myocardium is a rare form of cardiac rupture, caused by a hemorrhagic dissection among the spiral myocardial fibers, its diagnosis is rarely established before the operation or death, and extremely few cases have been reported in the literature and none of these cases seem to have a history of previous cardiac surgery which makes our report unique. Case Presentation. A 61-year-old female patient was admitted into the emergency room with complaints of progressive chest pain for 2 days. She had a history of second time prosthetic aortic valve replacement and was under anticoagulation therapy. She was diagnosed with an acute inferoposterior myocardial infarction and underwent emergency coronary angiography revealing spontaneous recanalization of the right coronary artery. During the follow-up, she developed cardiogenic shock and a new occurring systolic ejection murmur. Transthoracic echocardiography showed a left ventricular free wall rupture; then, she was taken in for emergency surgery. During the operation, a rupture zone and a wide intramyocardial dissecting area were detected. Intraventricular patch repair technic with autologous pericardial patch was used to exclude the ruptured area. Following the warming period, despite adequate hemostasis, hemorrhage around suture lines progressively increased, leading to the patient’s death. Conclusion. Pericardial adhesions might contain left ventricular rupture leading to intramyocardial dissection.